Genome-wide CRISPR/Cas9 screen identifies host factors for Newcastle disease virus replication - Tian, Jianxia; Wang, Ying; Zhou, Zijie; Li, Yuzhen; Chang, Chuanyu; Meng, Fanxing; Shi, Weiwei; Li, Hanlue; Wang, Weifan; Wei, Qiaolin; Liu, Haijin; Yang, Zengqi; et al. (Poultry science, 2025)
Viruses rely strictly on host factors to determine their susceptibility. Newcastle disease virus (NDV), an avian pathogen, can infect a wide range of avian, mammalian and human cell lines. However, NDV can only infect certain mammals and humans, and it does not cause disease in mammals or mice. A comprehensive identification of NDV-susceptible host genes that promote NDV infection is lacking. Here, we performed a mouse genome-wide CRISPR knockout (GeCKO) screening in murine fibroblast L929 cells infected with NDV. Fifty host genes were highly enriched in the screening. Using a viral minigenome assay and gene overexpression as well as single guide RNA (sgRNA) knockout, one of the genes was shown to predominantly promote viral replication. This gene is the solute carrier family 35 member A1 (SLC35A1), which is a cytidine monophosphate (CMP)-Sia transporter involved in the synthesis of sialic acid (SA). Knockout of SLC35A1 in L929 cells decreased the expression of the NDV receptors α2,3-SA and α2,6-SA on the cell surface, resulting in significant reductions in viral adsorption, internalization and replication. Furthermore, the knockout of a six-residue stretch, 82LGSPKE87, of SLC35A1 in cells specifically reduced the expression of the α2,6-SA receptor but not the α2,3-SA receptor, which decreased viral adsorption and replication. The reconstitution of SLC35A1 in the knockout cells completely recovered the α2,3-SA receptor, partially recovered the α2,6-SA receptor and almost completely recovered viral replication. In chicken fibroblast DF-1 cells, siRNA-mediated knockdown of chicken SLC35A1 reduced the expression levels of both the α2,6-SA and α2,3-SA receptors, decreasing viral replication. Our research indicated that SLC35A1 is a key host factor that promotes NDV replication. The CRISPR/Cas9 system can be used to identify essential host factors for the replication of intracellular pathogens. This study provides valuable insights into host susceptibility to NDV.